Keabsahan Pembulatan Nominal Pembayaran Oleh Petugas SPBU Di Daerah DIY Menurut Hukum Islam - Dewi Putri Mulyani; Riky Rustam (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is motivated by the rounding of prices that occurs when filling up fuel at gas stations, where rounding of prices also occurs even though the rupiah denominations are still in circulation, such as Rp. 200 and Rp. 500. This research examines the legality of rounding nominal payments by gas station officers according to Islamic law and analyzes the legal consequences of rounding off nominal payments by gas station officers according to Islamic law. This research uses normative research using a statutory and conceptual approach. This legal research is descriptive in nature, the data collection method is library research, then analyzed using qualitative analysis methods. The results of the research show that to round off nominal payments against rupiah denominations that are still in circulation, you must first obtain permission from the buyer. Rounding off nominal payments by gas station officers according to Islamic law is a type of defective contract, so that there are two legal consequences of a defective contract, namely, the contract can be canceled and can be null and void by law. As a result of the flawed contract above, Islamic law regulates the rights and legal remedies for the buyer as the injured party in the transaction, namely the right of khiyar. The suggestion from this research is that gas station officers should be more fair in rounding prices by confirming with buyers before rounding prices.